Management of Oxalis latifolia and Calystegia sepium in maize - Rahman, A.; James, T.K.; Mellsop, J.M.; Pyke, N. (New Zealand Plant Protection, 2002)
Fishtail oxalis (Oxalis latifolia) and pink bindweed (Calystegia sepium) are problem perennial weeds in maize crops Four field trials were conducted over two growing seasons to evaluate both cultural and chemical control methods The postemergence application of nicosulfuron provided good control of fishtail oxalis as did imazethapyr/imazapyr in imidazolinonetolerant maize Use of maize cultivars with strong early season growth or long staygreen attributes did not provide the expected reduction in oxalis bulb production Two trials with pink bindweed showed that the postemergence herbicides nicosulfuron dicamba and imazethapyr/imazapyr gave good control of this weed Postharvest crop management with stubble mulching cultivation or glyphosate treatment had little effect on pink bindweed but use of glyphosate as close as possible to maize planting significantly reduced the bindweed population